Porous Silicon in Microelectronics: From Academic Studies to Industry. (18th September 2015) - Gautier, Gael; Defforge, Thomas; Desplobain, Sebastien; Billoué, Jérôme; Capelle, Marie; Povéda, Patrick; Vanga, Kumar; Lu, Bin; Bardet, Benjamin; Lascaud, Julie; Seck, Cheikhou; Fèvre, Angélique; et al.
Abstract : The evolution of porous silicon (PSi) from its early studies in the late 70's toward its industrial application in microelectronics is described in this article. The way this material can be integrated now in many devices at a wafer level is shown in this paper through examples of prototypes that include PSi in their fabrication process. For instance, realization of devices on large area wafers in the field of RF passive components, energy micro-sources or porous flexible membranes are described. In this paper, we also show recent advances in the field of PSi etching and integration at an industrial level. In particular, we put an emphasis on reproducibility and homogeneity issues, on the wafer warp management using different annealing procedures.